1 pī saphān mittraphāp : khon N̜̄ong Khāi dai ʻarai : ʻēkkasan prak̜̄op kānsammanā, 6 Phrưtsaphākhom 2538 na Rōngr̄æm H̜̄olidē ʻIn M̄ækhōng R̜̄oyan Čhangwat N̜̄ong Khāi (H̜̄okankha Čhangwat N̜̄ong Khāi ; Nangsưphim Phūčhatkān Rāiwan, 1995)
Conference paper on problems caused by Thai-Lao Friendship Bridge in Nong Khai Province, Northeastern Thailand.